Evaluasi Keseimbangan Nutrisi Sapi Perah Betina Dewasa di UPTD Puskeswan Kota Padang Panjang - John Hendri; Alfian Asri (Jurnal Peternakan Mahaputra, 2020)
This study aims to evaluate the nutritional balance of adult female dairy cows at UPTD Puskeswan Padang Panjang. The livestock used in this study were all adult female dairy cows (who had given birth) from the Fries Holland breed that were kept in the breeding cage of UPTD Puskeswan Padang Panjang City with physiological status, namely 1 pregnant lactation, 5 non-pregnant cows and dry pregnant cages as much as 2 tails. The variables measured in this study were the consumption of dry matter (DM) feed, consumption of TDN, consumption of crude protein (CP) and consumption of calcium (Ca). The data obtained every day were then tabulated based on the range of consumption of DM, the range of TDN consumption, the range of CP consumption and the range of Ca consumption for dairy cows / head / day and then compared with the standards from the National Research Council (NRC) 1978 table. The analysis was carried out descriptively. Descriptive analysis was used to explain nutrient balance. From the results of the study it can be concluded: 1) dry matter consumption of all lactating cows and dry cows in pregnant cows is higher than the need, 2) consumption of TDN and calcium for lactating cows with milk production below 5 kg /head / day and dry cows with pregnant cows with body weight 400 kg is higher than the need, while the consumption of TDN and calcium from lactating cows with milk production above 5 kg / head / day and pregnant cows with a body weight of 500 kg is lower than the need and 3) consumption of crude protein (CP) of all lactating cows and pregnant pen dry cows with a body weight of 500 kg lower than the need, however the consumption of CP for pregnant cows with a body weight of 400 kg is higher than the need. In order to increase the productivity of the dairy cows that are kept, it is recommended that the managers of the UPTD Puskeswan Padang Panjang City improve the balance of forage and concentrate. To achieve a balance of 60% forage: 40% concentrate, fresh forage was given as much as 30.78 kg / head / day and concentrate was given as much as 20.52 kg / head / day.